Can students' emotional states influence their assessment of lecturers' performance? - Mohd Zaliman Mohd Yusoff,; Nurzeatul Hamimah Abdul Hamid,; Mazlyda Abd Rahman,; Nur Huda Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2012)
The Student Evaluation Form (SEF) is commonly used to assess lecturers’ teaching performance in the classroom. However, there are concerns that events that elicit emotion, such as students’ grades, could influence their assessment of their lecturers’ performance. Thus, we conducted a study to explore the effect of emotion-eliciting events on students’ emotional states and their assessment of lecturers’ performance. A random sample of 69 low- and high-ability students (26 control-group students and 43 experimental-group students) from Universiti Teknologi MARA, Johor, participated in this study. Two sets of questionnaires were used: the Positive and Negative Affect Scale and the SEF. The findings of the study indicate that especially for those with low ability, emotion-eliciting events affected students’ emotional states and their assessment of their lecturers’ performance.